1989
DOI: 10.1093/ije/18.3.546
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Childhood Cancer in Denmark 1943–1984

Abstract: A population-based study was carried out on 5790 tumours in children (aged 0-14 years) diagnosed in the period 1943-1984 in Denmark. Cases were identified from the files of the high-quality National Cancer Registry in which codes for tumours were based solely on topography until the end of 1977. To achieve a uniform data set following the outlines of the International Classification of Diseases for Oncology (ICD-O) coding system used by the Cancer Registry today, all cases of childhood cancer diagnosed prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Our study showed an overall age-standardized rate of 113.8 per million population, which is close to that reported from Britain and Japan but lower than that reported from the United States and Denmark 7,8,9 (Table 3). On the other hand, our results showed higher rates than those reported from Thailand, China and Philippines.…”
Section: Discussionsupporting
confidence: 81%
“…Our study showed an overall age-standardized rate of 113.8 per million population, which is close to that reported from Britain and Japan but lower than that reported from the United States and Denmark 7,8,9 (Table 3). On the other hand, our results showed higher rates than those reported from Thailand, China and Philippines.…”
Section: Discussionsupporting
confidence: 81%
“…However, the incidence rates of most other types of cancers in teenagers, including the leukaemias, have been unchanged for more than 4 decades. This indicates that environmental factors that have become prevalent in our industrialized society do not play any significant role in the aetiology of the majority of these cancers, as stated earlier for the group of childhood cancers (Brown et al, 1989).…”
Section: Discussionsupporting
confidence: 51%
“…Increasing trends with time were seen for malignant lymphomas in both boys and girls and for subtypes of non-seminoma germ-cell tumour among boys aged 15-19. For other diagnostic groups, including the main group of leukaemias, the rates have remained largely unchanged, suggesting that environmental factors associated with modern society play a minor role in the aetiology of cancer among teenagers.o 1993 Wiley-Liss, Inc.Although malignant tumours are less common among teenagers than in older people, in the late 1980s they were still the second most frequent cause of death in Denmark, accounting for approximately 15% of all deaths registered in the age group Age-specific rates for cancer show a distinct peak in the first 3 years of life, decrease to a minimum just before puberty, and then rise again throughout the remainder of the life span (Brown et al, 1989). In epidemiological studies it has become common practice to use the age of 15 as the boundary between childhood and adulthood.…”
mentioning
confidence: 99%
“…The low increase in risk seen for all tumour types combined since the 1940s has been described before5 and is due mainly to continuous increases in risk of lymphomas in boys and of neuroblastomas in both sexes.…”
Section: Commentmentioning
confidence: 68%
“…A national cancer registration system has been operating in Denmark since 1942 5. Regimens for administration of vitamin K to neonates have varied greatly over the 50 years of notification.…”
Section: Subjects Methods and Resultsmentioning
confidence: 99%